Estudo epidemiológico e imunohistoquímico com BAX, BCL-2 E P27 em carcinoma espinocelular invasivo da boca - Bezerra, Tarcísio Teobaldo (2007)
The evaluation of the expression of bax, bcl-2 and p27 proteins at invasive squamous cell carcinoma of oral cavity was done using the immunohistochemistry technique to know about apoptotic profile of these neoplasms. The epidemiological factors and the clinical behavior of the patients were detected, too. Statistical parameters different from odds ratio was employed for future comparisons. Forty-eight patients from Santa Casa da Misericórdia de Fortaleza, Ceará, Brazil was analyzed and with this analysis was possible to know the prognostic factors: sex of patients, instruction grade, familiar gains, tobacco consumption (form of consumption, duration of consumption, period of forsaking and quantity consumed), alcohol consumption (nature of drinking, duration of consumption, period of forsaking, quantity consumed, periodicity). In a posterior moment, with the histopathological report from the surgical specimen was possible to know about localization of neoplasm, size of neoplasm, histological grade, nodes involvement and invasiveness. Pieces of the neoplasm were achieved from surgical specimen and glass slides were done to analyze the invasiveness by hematoxilin-eosin coloration. After the immunohistochemistry reaction by streptoavidin biotin technique was done to evaluate the expression of proteins above. The glass slides with positive reaction were submitted under a counting and, at least, one thousand cells were counted. The results from counting were submitted under the LI(Labelling Index) and HS(H Score) methods. The evaluation of the results was made using descriptive methods and the statistical tests were qui-square and Fisher’s exact test with 10% significance. The results showed the mean age was 57 years old, more males than females, analphabets and one minimum wage the mean familiar gain. The main form of tobacco consumption was industrialized cigarette with 20 years of consumption. The swallow of distillers drinking was bigger than fermentation ones with 20 years of drinking at mean. The floor of the mouth was the anatomic site with more number of cases and the mean size of neoplasm was 1.4 inches. The preponderant pathological staging detected was pT2 and the preponderant histological grade was moderately differentiated. Among the cross tabs realized, there were statistical correlation between size of tumors and age (P=0.084; α=10%), between size of tumors and nodes involvement (P=0,085; α=10%), between sex of patients and nodes involvement (P=0.03; α=10%). The results from immunohistochemical reactions were more positive to bax (77.1% of positive cases), P27(45.9% of positive cases) and bcl-2 (16.6% of positive cases). The mean of LI showed bax at first position (67.766); second bcl-2 (10.804) and P27(7.989). The cross tabs among HS showed statistical positive correlation between bax and P27 (0.245 at Pearson’s correlation). The statistical parameters were: mean and its standard error, median, mode, standard deviation, kurtosis and its standard error, minimum, maximum and percentiles. The conclusions showed apoptosis propensity at oral squamous cell carcinoma